Analisis Kemampuan Komunikasi Interaktif Pada Proses Pembelajaran di Kelas III SDN 09 Tanjung Lay - Sulianna, Atira; Mastiah, Mastiah; Khoiri, Ahmad (STKIP Melawi, 2025)
Abstrak: The formulation of the problem in this research is what is the factor in the lack of interactive communication activities and what is the appropriate strategy to overcome the lack of interactive communication that occurs in the learning process in class III at SDN 09 Tanjung Lay. The aim of this research is to find out a complete description of interactive communication. The subjects in this research were teachers and students of class III SDN 09 Tanjung Lay. The object of the research is interactive communication that occurs between teachers and students during the learning process in class III at SDN 09 Tanjung Lay. This research uses qualitative research methods. Descriptive qualitative design. Descriptive approach. The researcher carried out the following stages: Research Preparation, Research Implementation, Final Research This research will be carried out in class III of SDN 09 Tanjung Lay, Nanga Pinoh District, Melawi Regency. The research is planned for May 2022/2023 academic year. Data Collection Techniques Data was obtained from various sources using triangulation techniques. The data collection techniques used are interviews, observation, documentation of the teacher's less varied delivery of material which is a significant obstacle, the communicator (teacher) is impatient with students who are not yet able to respond quickly to understand the material, and the media is less interesting in creating interactive learning. so that learning feels boring and students are not interested in participating in the learning process, so this causes students' attention to be divided, starting from students who enjoy playing alone and students who enjoy chatting with their classmates. Strategies used by teachers for optimal interactive communication in the learning process: Starting good meetings, knowing students' interests and characters, using learning while playing methods, conducting questions and answers, discussing, using good language, and building cohesiveness in the class.Keywords: Communication, Interactive and Learning.Abstrak: Tujuan penelitian ini untuk mengetahui deskripsi lengkap mengenai komunikasi interaktif. Rumusan masalah dalam penelitian ini adalah apakah yang menjadi faktor dari kurangnya aktivitas komunikasi interaktif dan Bagaimana strategi yang tepat untuk mengatasi kurangnya komunikasi interaktif yang terjadi pada proses pembelajaran dikelas III SDN 09 Tanjung Lay. Subjek dalam penelitian ini adalah guru dan siswa kelas III SDN 09 Tanjung Lay. Objek penelitian adalah komunikasi interaktif yang terjadi pada guru dan siswa pada saat proses pembelajaran berlangsung di kelas III SDN 09 Tanjung Lay.Penelitian ini menggunakan metode penelitian kualitatif. Desain kualitatif deskriptif. Pendekatan deskriptif. Peneliti melakukan tahapan berikut: Persiapan Penelitian, Pelaksanaan Penelitian, Akhir Penelitian Penelitian ini dilaksanakan di kelas III SDN 09 Tanjung Lay Kecamatan Nanga Pinoh Kabupaten Melawi. Penelitian direncanakan pada bulan Mei tahun ajaran 2022/2023. Teknik Pengumpulan Data data diperoleh dari berbagai sumber dengan menggunakan teknik trianggulasi. Teknik pengumpulan data yangÂ Â digunakan adalah wawancara, observasi, dokumentasiÂ penyampaian materi yang kurang bervariasi dari guru menjadi hambatan yang signfikan, komunikator (guru) kurang sabar terhadap murid yang belum mampu tanggap cepat memahami materi, serta media yang kurang menarik dalam menciptakan pembelajaran yang interaktif, sehingga pembelajaran terasa membosankan dan siswa tidak tertarik mengikuti proses pembelajaran, sehingga hal tersebut membuat perhatian siswa bercabang, mulai dari siswa asik bermain sendiri dan siswa yang asik ngobrol dengan teman sebangkunya. Strategi digunakan guru agar komunikasi interaktif proses pembelajaran optimal: Mengawali pertemuan yang baik, mengetahui minat dan karakter siswa, menggunakan metode belajar sambil bermain, melakukan tanya jawab, berdiskusi, menggunakan bahasa yang baik, dan membangun kekompakan dalam kelas.Kata Kunci: Komunikasi, Interaktif dan Belajar